Multi-Hazard Zonation For Effective Management of Disasters in Tamil Nadu - A. Balasundareshwaran; K. Kumaraswamy; K. Balasubramani (Geosfera Indonesia, 2020)
Natural hazards are a long existing threat to human and their surroundings which may occur throughout the world. Tamil Nadu is one of the Indian States with a number of natural hazard incidences. The occurrence of natural hazards, such as cyclone, storm surge, flood, drought, landslide, forest fire etc., has increased manifold in the recent decades.The multi-hazard zonation is one of the preliminary studies in disaster management scenario, which is used to understand the product of all prominent natural hazards. At the state level, it is imperative for the government to know the regions affected by multiple hazards to help them prepare the management plans appropriately to protect the local communities and infrastructures. However, such systematic hazard assessment and integration in an administrative unit is largely missing in Tamil Nadu. Further, the utilisation of geoinformatics in the preparation of multi-hazard zonation helps to identify the most endangered areas of the State precisely and offers insights to detailed studies in highly risk zones. This paper attempts on these lines to prepare Multi Hazard Zones (MHZ) based on natural hazards viz. earthquake, landslide, cyclone, storm surge, flood, drought and forest fire of Tamil Nadu. The data for the study were generated from multiple sources, which were all generalised and integrated in a normalised scale. The occurrences, intensities and frequencies of hazards, namely seismic, landslide, and forest fire are the reasons for a very high multi-hazard in hilly tracts of the Nilgiris and parts of Shayadhri hills in Coimbatore and Theni Districts, whereas cyclone, storm surge, and flood caused a very high risk along the coastal stretch of Chennai, Kancheepuram, Cuddalore and Ramanathapuram Districts. The segregation of the results into administrative division’s which was then categorised in an order of high risk zones may provide a powerful tool to the State authorities to allocate fund and resources. The output of this study also offers zonation for immediate knowledge, policy briefs, and proper disaster management plan at State level. Keywords : Disaster Management; Natural Hazards; Geoinformatics; Tamil Nadu Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License